Prevalence and Risk Factors of Iron Deficiency Anemia in Children with Atopic Dermatitis - Mahir Serbes; Elif Güler Kazancı (Galenos Publishing House, 2024)
Objective: Refraining from intake of allergic foods, chronic inflammation and immunosuppressive drug use are factors associated with anemia in atopic dermatitis (AD). In this study, we aimed to investigate the frequency of iron deficiency anemia (IDA) and comorbid risk factors affecting this frequency in children with AD. Method: The medical records of 100 children aged 0-6 years with AD (patient group) and 100 healthy children of the same age group without AD (control group) were treated in Sivas Numune State Hospital from May 2019 to October 2019 were retrospectively analyzed. Results: In our study, the frequency of AD in children with AD (15%) was significantly higher than in healthy children (5%) (p<0.001). Early-onset AD, increased SCORAD severity index scores, concomitant food sensitivities, especially multiple food sensitivities, asthma, skin infection, breastfeeding for more than 6 months and presence of multiple atopic conditions were associated with a higher frequency of AD in children with AD. However, hay fever, family history of atopy, exposure to cigarette smoke, large family size, consanguinity and parental socioeconomic status were not significantly associated with a higher prevalence of AD in children with AD. Conclusion: The prevalence of AD was significantly higher in children with AD compared to healthy children. Therefore, improving clinicians' self awareness of screening and monitoring for AD in children with AD is essential to minimize the burden of AD disease. More comprehensive further studies are needed to investigate the link between IDA and AD and relevant influencing factors.